Multiple Dense Papules on the Entire Glans: Profound Pearly Penile Papules - Li H; Tian Q; Shan X; Wang Z; Fang X (Dove Medical Press, 2023)
Huixian Li,1 Qinghua Tian,2 Xiujuan Shan,2 Zhenhua Wang,2 Xiangang Fang2 1Department of Sterilization Supply, Weifang People's Hospital, Weifang, Shandong, People's Republic of China; 2Department of Dermatology, Weifang People's Hospital, Weifang, Shandong, People's Republic of ChinaCorrespondence: Xiangang Fang, Department of Dermatology, Weifang People's Hospital, 151 Guangwen Street, Weifang, Shandong, 261041, People's Republic of China, Tel +86-0536-8192561, Email sdlntszqjlb@163.comAbstract: A 23-year-old man presented for evaluation of multiple dense asymptomatic papules on the entire glans. Histologically, the lesions resembled acral angiofibroma. A diagnosis of profound pearly penile papules was made. This is the third reported case and more serious and typical than described in previous reports.Keywords: pearly, penile papules, profound